Faktor-Faktor yang Mempengaruhi Agresivitas Pajak di Indonesia - Tiyana Rahayu; Riana Rachmawati Dewi; Dimas Ilham Nur Rois (Journal of Economic, Bussines and Accounting (COSTING), 2023)
One of the reasons for not achieving the target of tax revenue in Indonesia is due to tax aggressiveness. The high tax burden that must be paid is a factor driving aggressive companies towards taxes. Efforts to avoid taxes are carried out in various ways. However, excessive tax avoidance will harm the state. Many factors trigger the emergence of tax aggressiveness. So, researchers want to examine further the effect of capital intensity, inventory intensity, company size, institutional ownership, and gender diversity on tax aggressiveness. Researchers chose mining sector companies listed on the IDX 2017-2021 as the study population. There were 7 selected company samples after taking samples using the purposive sampling technique. Data processing was carried out using Views software version 9. After researchers collected quantitative data, the researcher performed a panel data regression analysis using a random effect model. Thus, this study proves that the variable capital intensity and inventory intensity affect tax aggressiveness. Meanwhile, the variable firm size, institutional ownership, and gender diversity do not affect tax aggressiveness. Keywords: Capital Intensity, Inventory Intensity, Firm Size, Institusional Ownership, Gender Diversity, And Tax Aggressiveness.